Malignant Self-Regard in clinical outpatient samples. (August 2018) - Huprich, Steven K.; Macaluso, Matthew; Baade, Lyle; Zackula, Rosalee; Jackson, Jennifer; Kitchens, Rebecca
Highlights: MSR is associated with levels of personality functioning and DSM-5 personality traits. MSR incrementally predicts relationship quality above DSM-5 personality traits. MSR incrementally predicts levels of personality functioning above DSM-5 personality traits. MSR incrementally predicts DSM-5 personality traits above levels of personality functioning. Abstract: While the malignant self-regard construct and a corresponding questionnaire, the Malignant Self-Regard Questionnaire (MSRQ; Huprich, 2011) have been empirically evaluated in several non-clinical samples, it has yet to be evaluated in a clinical population. In this study, 139 outpatients in the Departments of Psychiatry and Behavioral Sciences ( n = 83) and Internal Medicine ( n = 57) were administered the MSRQ and a number other measures to assess its construct and incremental validity. The MSRQ was internally consistent in both samples, and was positively correlated with four dimensions of levels of personality functioning, DSM-5 personality trait domains, overdependence, detachment, insecure attachment, and general perceptions of physical and mental well-being. Furthermore, the MSRQ incrementally predicated variance in levels of personality functioning, interpersonal dependency, and general perceptions of physical and mental well-being above and beyond DSM-5 traits and (where appropriate) levels of personality functioning. These findings converge with studies of the MSRQ in nonclinical samples and support the clinical utility and validity of the MSRQ for further use.